Pengaruh Pemahaman Akuntansi, Persepsi Pelaku, Omset dan Besaran Modal Terhadap Penyusunan Laporan Keuangan pada UMKM di Kota Jambi - Ariani, Lia; Mukhzarudfa, Mukhzarudfa; Gowon, Muhammad (Ekonomis: Journal of Economics and Business, 2024)
MSMEs have a considerable role in the economy in Indonesia, which was proven during the Covid 19 pandemic crisis, where in the midst of that crisis MSMEs were able to survive. Apart from that, MSMEs also have their own problems, especially internal problems related to recording financial statements. This study aims to analyze the influence of accounting understanding, actors' perceptions, turnover and amount of capital on the preparation of financial statements for MSMEs in Jambi City. This study uses primary data obtained by distributing questionnaires to MSMEs in the field of trade and industry in 11 districts in Jambi City. This study selected 100 samples with determination using stratified random sampling. This study used Multiple Regression Analysis method with SPSS 26. The results of this study show that the understanding of accounting, turnover and amount of capital affect the preparation of financial statements in MSMEs, while the perception of actors does not affect the preparation of financial statements in MSMEs.